2014
DOI: 10.20961/agsjpa.v16i2.18920
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Sifat-Sifat Agronomi dengan Hasil dan Kandungan Antosianin Padi Beras Merah

Abstract: Brown rice is a type of rice can be grown on land that is less water (upland). Brown rice has anthocyanin as an antioxidant. The purpose of this study was to identify brown rice agronomics characters that can be used as selection criteria to obtain brown rice which high anthocyanin. The experiment was conducted at the greenhouse of Agriculture Faculty, UNS using completed randomized block design consisting of 5 local varieties namely Mandel Wonogiri, Segreng Gunung Kidul, Segreng Boyolali, Segreng Wonogiri 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…However, height of the rice plant was positively correlated with dry straw weight, while dry straw weight also had positive correlation (p<0.05) with grain yield and other variables including numbers of tillers, panicles, and filled grains, as well as 100-grain weight (Table 2). Other study also indicated positive correlation between grain yield and 1000-grain weight, panicle length, grain number per panicle, total tillers, and panicle number per clump [17].…”
Section: Resultsmentioning
confidence: 75%
“…However, height of the rice plant was positively correlated with dry straw weight, while dry straw weight also had positive correlation (p<0.05) with grain yield and other variables including numbers of tillers, panicles, and filled grains, as well as 100-grain weight (Table 2). Other study also indicated positive correlation between grain yield and 1000-grain weight, panicle length, grain number per panicle, total tillers, and panicle number per clump [17].…”
Section: Resultsmentioning
confidence: 75%
“…Both have the same strong influence on grain yields. According to [39] said that the correlation coefficient which shows a large number close to +1 means that it has a close relationship between the observed characters. The maximum number of offspring with a P-Value of 0.049 with a correlation value of 0.446 can be said to have a significant effect on a rather weak correlation.…”
Section: Resultsmentioning
confidence: 99%
“…Correlation coefficient that shows a large number close to +1 or -1 can be used as the basis for selection criteria. This is because the correlation coefficient, which shows a large number, means that it has a close relationship between the observed characters [17].…”
Section: Correlation Between Charactersmentioning
confidence: 99%